Evaluation of Handmade Toggle Pin Technique for the Repair of Coxofemoral Luxation in Dogs - Jekinakatti, Kanteshkumar Mahadev; D R, Manjunatha; D, Vilas; Balappanavar, B R; N M, Rajashailesha; G K, Chetan Kumar; Ballari, Shashidhar; N, Nagaraju; M N, Ramya (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The clinical study was conducted to evaluate the handmade toggle pin technique for the repair of coxofemoral luxation in six clinical cases of dogs of either sex. Dogs were brought with a history of limping and non-weight bearing lameness due to automobile trauma and jump from height. Orthopaedic and radiographic examinations confirmed craniodorsal coxofemoral luxation in all dogs. Under general anaesthesia luxation was stabilised with toggle pin technique using toggle pins via craniodorsal approach. Post-operatively a pelvic bandage, Amoxicillin @ 12.5 mg/kg, Carprofen 4.4 mg/kg and tablet Deep TBR for five days was followed, and limited activity with short leash walk was advised. Intra-operative and post-operative complications were not observed with respect to reluxation, toggle pin breakage and nylon thread breakage. Post-operative radiographic evaluation revealed proper alignment and anatomical configuration of coxofemoral joint, toggle pins were in position, no arthritic changes were observed in the acetabulum and femoral head. All dogs showed excellent weight bearing and limb usage on 30th post-operative day onward. In conclusion clinical results were excellent in dogs and handmade toggle pin technique was found to be easy, simple, economical and practical method for the repair of coxofemoral luxation in dogs.